HUBUNGAN PELAKSANAAN MANAJEMEN LAKTASI DINI DENGAN WAKTU KELUARNYA ASI PADA IBU PASCA PARTUM DI RUMAH BERSALIN ANANDA MOJOKERTO - Triwibowo, Heri; Prasastia Lukita Dewi, Catur (JURNAL KEPERAWATAN BINA SEHAT, 2009)
This Research is based on there are many ASI that late to out more than 2 days, four days, and even more than a week postpartum. This matter can cause problem for mother postpartum and newborn baby. One of this efforts is to overcome expenditure slowness ASI with early laktasi management.The aim of this Research is to know the connection of early laktasi Management with time of ASI out in post partum mother at Ananda Midwifery Clinic In Mojokerto. Kind of this Research is corelational detect to detect early laktasi management connection with time of ASI outcome. This Research start from 13 Augusts 2008 up to 13 Septembers 2008 to 21 mother groups that do early laktasi management in its entirety and appropriate, with 13 mother groups that done early laktasi management incomplete or inappropriate protap. Collecting data by observation. Data is analyzed statistically by using chi square statistics test in standard of belief 95% and used mistake standard (a) as big as 0,05.Result of this research is mother that done early laktasi management in its entirety and protap appropriate 76,19 % ASI out fast that is in range of time less than 24 hours post partum. For mother that done incomplete or inappropriate protap early laktasi management 84,62% ASI out slow that is in range of time less than 24 hours postpartum. Statistics chi square test value got result x² count > x² table (11,894 > 3,841, so h0 aversed and h1 accepted thereby there connection between early laktasi management with time of ASI out in post partum mother at Ananda Midwifery Clinic in MojokertoBased on this result suggested to midwife and nurse at Midwifery Clinic that could do Midwifery Clinic policy that already have with the procedure that appointed, so ASI in post partum mother is not retarded and ASI out fastly.Keyword: Early laktasi management, time of ASI out.